2021
DOI: 10.3389/fped.2021.637275
|View full text |Cite
|
Sign up to set email alerts
|

Management of Follow-Up With Preterm Infants During the Outbreak in China

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) swept Wuhan in January 2020. Other cities in China also suffered during the pandemic. Routine medical services were conducted in the Neonatal Intensive Unit (NICU) as usual, but the follow-up after discharge was seriously affected.Objective: To investigate the feasibility and effectiveness of a combination of online and face-to-face follow-up for preterm infants during the COVID-19 epidemic and to explore a follow-up pattern that can provide follow-up services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 16 publications
(14 reference statements)
0
28
0
2
Order By: Relevance
“…The important components and findings of the final included articles are presented in Table 1. Results of the study showed that included studies had a focus on different participants, including Parents, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] infants, 26 and nurses. 15,16 Several countries were engaged in the studies, including Nordic countries including Sweden, 10,[13][14][15]23 Denmark, 12,13,26 Iran, [17][18][19][20][21][22] China, 23 and the USA.…”
Section: General Characteristics Of Reviewed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The important components and findings of the final included articles are presented in Table 1. Results of the study showed that included studies had a focus on different participants, including Parents, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] infants, 26 and nurses. 15,16 Several countries were engaged in the studies, including Nordic countries including Sweden, 10,[13][14][15]23 Denmark, 12,13,26 Iran, [17][18][19][20][21][22] China, 23 and the USA.…”
Section: General Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…Results of the study showed that included studies had a focus on different participants, including Parents, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] infants, 26 and nurses. 15,16 Several countries were engaged in the studies, including Nordic countries including Sweden, 10,[13][14][15]23 Denmark, 12,13,26 Iran, [17][18][19][20][21][22] China, 23 and the USA. 25 The majority of studies had a quantitative approach, including interventional, 11,[15][16][17][18][19][20][21][22] and the rest were qualitative, [12][13][14]24 observational 26 prospective, 23 and retrospective cohorts.…”
Section: General Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…Gavazzi et al [ 16 ] showed the feasibility of video consultations for standardized measurement instruments, such as the Gross Motor Function Measure–88, in a pediatric group with chronical neurological disease. Li et al [ 20 ] showed that a combination of follow-up visits that were face-to-face and via video allowed a follow-up rate that was as high during the first wave of the COVID-19 pandemic in April 2020 as in the previous year. In this study, due to the additional offer of a video consultation, the rate of follow-up appointments decreased slightly, but the total number of consultations increased.…”
Section: Discussionmentioning
confidence: 99%
“…A pandemia da Covid-19 trouxe inúmeras repercussões para a assistência prestada às crianças nascidas prematuras, como observado em estudos nacionais e internacionais que identificaram interrupção no acompanhamento de lactentes prematuros após a alta hospitalar, devido à paralização momentânea dos serviços de seguimento, com consequência para a descontinuidade da atenção à saúde prestada à essa população 10,11 .…”
Section: Introductionunclassified